PENGARUH PERTUMBUHAN PERUSAHAAN, DIVIDEN, PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2021 - Laia, Ricardo Arman; Hulu, Oktavianus Otonius; Rahmi, Namira Ufrida; Nasution, Muhammad Irsan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The main objective of the company is to enhance the overall value of the company. This increase in value then impacts the welfare of employees, thereby influencing the long-term valuation of the organization. Researchers aim to investigate the elements affecting the high valuation of manufacturing businesses listed on the Indonesia Stock Exchange (IDX) during the period 2016-2022. This research examines several independent factors, including company growth, dividends, profitability, and capital structure. The dependent variable studied is the company's value. This study utilizes secondary data derived from the annual financial reports issued by manufacturing companies during the period 2016-2021, obtained from the official website of the Indonesia Stock Exchange. The research employs a research methodology utilizing quantitative techniques, particularly simple linear regression and multiple linear regression, as the primary research methods. The study focuses on the research population, namely manufacturing companies listed on the Indonesia Stock Exchange during the period 2016-2021. The sample size for this study consists of a total of 12 companies. The research findings indicate that company expansion has a detrimental impact on company value, while dividends have a beneficial effect in increasing company value. Furthermore, profitability is proven to have a significant positive relationship with company value, and capital structure also appears to have a significant positive impact on company value. Additionally, the simultaneous testing conducted, either jointly or simultaneously with the dependent variable, shows that all independent factors examined in this study have statistically significant and positive impacts on the dependent variable, namely company value.